Hábitos de estudio y comprensión lectora en estudiantes del cuarto grado de primaria del colegio parroquial Sagrada Familia, Belén 2022 - Correa Tafur, Yngrid Oriana (2023)
The research asked the following question: What is the relationship between study habits and reading comprehension of the fourth-grade students of the Sagrada Familia Parochial School, Belén district in 2022? and as an objective to relate the study habits and reading comprehension in the same students of the aforementioned educational institution. The type of research applied was relational because it was consistent with the objective, in addition, the bivariate, field, and cross-sectional design was applied. As a population and sample, 94 students from the educational institution were taken, in addition, the survey and questionnaires were used as a technique and data collection instruments. The questionnaires were validated by expert judgment. Spearman's correlation shows that there is a statistically significant relationship between the variable level of study habits and the reading comprehension of the fourth-grade primary school students of the Sagrada Familia Parish School, (r=0.873**; Sig. < 0.01). Thus, the research hypothesis is confirmed.